2008
DOI: 10.1002/hed.20858
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value for malignancy in the finding of microcalcifications on ultrasonography of thyroid nodules

Abstract: This study suggests that microcalcifications were highly specific for malignancy and were present in 61% of the malignant nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 17 publications
1
22
1
Order By: Relevance
“…However, only seven cases of malignancy were detected in that study and surprisingly only 4% in the second group presented these characteristics (9). In the present study using characteristics of high specificity (17)(18)(19)(20), although only 11.4% of the nodules presented these findings, the chance of malignancy in a second FNAC exam was approximately 17%. Although the FNAC was not repeated in the case of non-suspicious nodules considering this proportion of suspicious nodules, the frequency of malignancy in this group and an overall malignancy rate of approximately 2% upon repeat FNAC (3,4,6-9) it was concluded that specifically in these cases (non-suspicious nodules) malignancy should be negligible.…”
Section: Resultscontrasting
confidence: 60%
See 1 more Smart Citation
“…However, only seven cases of malignancy were detected in that study and surprisingly only 4% in the second group presented these characteristics (9). In the present study using characteristics of high specificity (17)(18)(19)(20), although only 11.4% of the nodules presented these findings, the chance of malignancy in a second FNAC exam was approximately 17%. Although the FNAC was not repeated in the case of non-suspicious nodules considering this proportion of suspicious nodules, the frequency of malignancy in this group and an overall malignancy rate of approximately 2% upon repeat FNAC (3,4,6-9) it was concluded that specifically in these cases (non-suspicious nodules) malignancy should be negligible.…”
Section: Resultscontrasting
confidence: 60%
“…Although this imaging method alone does not define the etiology of the nodule it assists in the differentiation between benign and malignant nodules (10,(17)(18)(19)(20). This fact renders ultrasonography a highly attractive tool for the selection of candidates for repeat FNAC in the case of an initial benign cytological diagnosis, but its validation for this purpose is fundamental.…”
Section: Discussionmentioning
confidence: 99%
“…Although, microcalcifications are known to be strongly associated with malignant nodules, the association of macrocalcifications with malignancy is controversial (8)(9)(10)(11)(12)(13)(14)(15). Recent studies have revealed a relationship between macrocalcification and malignancy, particularly in papillary thyroid carcinomas (9,10,(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…When microcalcification is noted within a solitary thyroid nodule the risk of malignancy is very high. It is present in 61% of the malignant nodules [3]. Any suspicious thyroid lesion, even tiny lesions should be investigated by fine needle biopsy.…”
Section: Discussionmentioning
confidence: 99%